Anamorfoses na Música Eletroacústica Mista - Gati, Tiago C. Mantovani [UNESP] (2014)
One of the most recurring and essential issues of mixed electroacoustic music lies in the distortions – anamorphosis – that result from the interaction of a performer with electroacoustic means, ambiguous situations in which not only the nature of a sound source is veiled, but also the process through which this sound might have gone through. In the performance of mixed pieces, sounds and visual images trigger intricate connections with the public, and anamorphosis acts in between a more direct audiovisual relationship – what is seen in gestural terms is coherent with what is heard – and an “illusory” one – what is seen does not relate immediately to what is heard. Cases considered representative in the repertoire of mixed pieces, the analysis of two works (Parcours de l’Entité, by Flo Menezes, and Altra voce, by Luciano Berio), and the practical investigation in two composed pieces contribute to investigate anamorphosis in the realm of instrumental gesture as well as in the dynamics of the performance, given the fact that extra-musical elements are often used by composers to emphasize such distortions.